Baetis jaervii sp. n. (Ephemeroptera: Baetidae) from northern Europe - Savolainen, Eino (Entomologica Fennica, 2009)
Baetis jaervii sp. n. is described and illustrated. The history and relationships of this taxon to related species are elucidated on the basis of literature and determinations of genetic distance and mtDNA barcodes. B. jaervii is the only representative of the B. vernus group found in northern Europe, the nymphs of which live in lakes. The population from northern Finland earlier assigned to Baetis tracheatus should be transferred to represent B. jaervii.